Identidades e performatividade de gênero nas práticas discursivas da Brahma Kumaris. - Silva, Daniel do Nascimento e (Cadernos de Linguagem e Sociedade, 2010)
The present paper undertakes a theoretical and critical analysis of the question of gender within Brahma Kumaris discursive practices and makes its critique in line, basically, with the thought of Judith Butler. The interdisciplinary fi eld of gender studies argues that gender is the very condition of possibility for subjectivity, thus being invested with social and political connotations. However, the traditions, both secular and religious, tend either to obliterate or to naturalize gender. By adopting the theoretical and methodological framework of Social and Cultural Pragmatics (Rajagopalan, 2000; Pinto, 2002), this paper attempts to critique the elision of gender within Brahma Kumaris discourse, and, in doing so, tries to address the question of performativity that is implied in recent critical approaches of the social and human sciences when focusing the question of gender.